Mapping the Landscape of Chemical Thinking Research: A Comprehensive Scopus Based Analysis - Mellyzar, Mellyzar; Nahadi*, Nahadi; Hernani, Hernani; Supriatna, Asep; Lee, Tien Tien (Jurnal IPA & Pembelajaran IPA, 2025)
Research on chemistry education has consistently centered on students' conceptual and procedural knowledge. However, there is a clear need to prioritize how learners apply chemical thinking to address complex real-world problems. This gap highlights the need to understand how students and teachers connect molecular-level reasoning with broader social, ethical, and environmental contexts. A systematic review is the clear solution to address this issue. It will map trends, gaps, and strategies that foster the development of chemical thinking. This study provides a comprehensive overview of chemical thinking research in chemistry education through bibliometric and thematic analysis. A total of 59 scopus-indexed articles published between 2012 and 2025 were analyzed using the bibliometrix package in R and the biblioshiny interface. The analysis focused on publication trends, thematic evolution, collaboration networks, and instructional strategies. The results are clear: most studies target secondary and undergraduate learners, emphasizing causal reasoning, structure, property relationships, and representational competence. However, there are significant gaps in research concerning preservice teachers, assessment practices, and contextual approaches such as project-based and socio-scientific learning. Future studies must integrate reasoning, modeling, and sustainability-oriented frameworks. Effective strategies include inquiry-based, reflective, and socially relevant approaches. These approaches promote conceptual understanding and ethical reasoning. They offer valuable guidance for curriculum innovation and teacher education in chemistry